A Case Report on Parathyroid Carcinoma: A Diagnostic Dilemma (Bangladesh Journal of Nuclear Medicine, 2019)
Parathyroid Carcinoma is a rare cause of primary hyperparathyroidism. Pre-operative diagnosis remains a challenge. Here we report a case referred to us for suspicious goiter with hypercalcemia. Cytological findings suggested it to a possible thyroid mass rather than parathyroid neoplasm. Serum parathormone level was high and the patient underwent surgery. Histopathology confirmed the diagnosis of parathyroid carcinoma. A diagnostic approach to parathyroid neoplasm, combining multimodality imaging and clinico-pathologic features, is discussed. Bangladesh J. Nuclear Med. 21(2): 122-124, July 2018